Regionalism and Governance in the Americas
XXVII, 284 p.
Keywords: This book links contemporary thinking on global and regional governance to the recent experience of the Americas. It offers fresh insights into understanding the processes of order and change in the region, and in the broader international system. A particular concern is to reveal the changing contours of regional governance, whether in terms of actors, issue areas and relations with global structures.